RESEARCH AND DEVELOPMENT PROCESS OF PENETRATE CORE LITERACY-THE ROTATION AND TRANSFORMATION OF GRAPHICS AS AN EXAMPLE - Su, Yuchan; Haiyan Zhang (JOURNAL OF SONGKE MATH, 2023)
This paper focuses on solving problems from line and difference problems, proving angle problems and common vertex problems using rotational transformation ideas to expand the problem-solving process and develop students' core literacy. After analyzing the mathematics test questions, it is not difficult to find that the rotation of a figure is often tested in a comprehensive expansion. The test questions focused on the problems related to angles or line segments when the figure is rotated to a particular position, integrating the dynamic geometry of change and invariance, geometric conjecture, drawing, reasoning, proof and calculation ability, as well as innovation and practical abilityof students' experience of the operation activities related to the transformation of a figure. The solution of such problems requires intuitive imagination, logical reasoning and mathematical literacy. After rotation, the figure and the original figure are congruent, therefore, the method of rotational change becomes a new way of thinking in solving mixed problems with complex figures, and it is easier for students to understand the idea of doing the problem by rotating and transforming the figure to construct auxiliary lines.